Pengembangan Perangkat Pembelajaran Fisika Berbasis Masalah untuk Meningkatkan Hasil Belajar dan Sikap Ilmiah Mahasiswa - I Wayan Gunada; Hairunnisyah Sahidu; Sutrio Sutrio (Department of Physics Education, Universitas Mataram, 2015)
This study aims to develop problem-based learningÃÂ device in terms ofÃÂ validity and student responses. Learning device was developed coveringÃÂ the syllabus, lesson plans, fundamental of physicsÃÂ textbook, exsperiment in fundamental physics , worksheets, and learning outcome test. The expected benefits of this research is the problem-based learning tools that can be used as an alternative to the lecturer of the fundamental of physics learning in FKIPÃÂ Mataram of University.This refers to the process of developing 4D models (define, design, develop, disseminate). The results validate the lecturer learning device consisting of a syllabus, lesson plans, fundamental of physicsÃÂ textbook, experiment in fundamental physics , worksheets, and learning outcome test successivelyobtained scores of 2.65, 2.68, 3.30, 3.25, 2.285 and 3.14 are decent categorized. Student learning outcomes is seen from indicators of student achievement of cognitive learning and experiment processes valueÃÂ row gets a percentage of 76.80%ÃÂ and 78.50%, while the scientific attitudeÃÂ students which amountedÃÂ average value of 76.42 and scientific attitudeÃÂ students can be interpreted good categorized. The positive student responses which amounted to 85.90%. From the validation results, student learning outcomes and student responses can be interpreted decentÃÂ device.